2017
DOI: 10.1097/md.0000000000009535
|View full text |Cite
|
Sign up to set email alerts
|

The side effects and complications of percutaneous iodine-125 seeds implantation under CT-guide for patients with advanced pancreatic cancer

Abstract: The side effects and complications frequently occur in implantation of I-125 seeds for patients with advanced pancreatic cancer. More concern should be given to the patients treated by this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…125 I seed implantation is not a new radiotherapy technique; it was used initially to treat prostate cancer, and its e cacy in local tumor control is well documented [14]. Per some investigations, percutaneous 125 I seed implantation combined with chemotherapy to treat pancreatic cancer under CT guidance is a safe and effective method for treating LAPC; patients with advanced pancreatic cancer implanted with 125 I particles had fewer incidences of postoperative side effects and complications [12,13]. A series of preliminary studies have shown that 125 I seed implantation may bene t patients in pain relief, control of local tumor growth, and survival [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…125 I seed implantation is not a new radiotherapy technique; it was used initially to treat prostate cancer, and its e cacy in local tumor control is well documented [14]. Per some investigations, percutaneous 125 I seed implantation combined with chemotherapy to treat pancreatic cancer under CT guidance is a safe and effective method for treating LAPC; patients with advanced pancreatic cancer implanted with 125 I particles had fewer incidences of postoperative side effects and complications [12,13]. A series of preliminary studies have shown that 125 I seed implantation may bene t patients in pain relief, control of local tumor growth, and survival [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Ablation techniques include radiofrequency ablation (RFA), microwave ablation (MWA), cryoablation and irreversible electroporation (IRE). NS not specified, US ultrasound, CT computed tomography, R retrospective, P prospective, FFX FOLFIRINOX, SAE serious adverse event, mOS median overall survival from diagnosis (mOSd) or treatment (mOSt) Authors Year, design Technique(s) Approach, image-guidance Number of LAPC patients Severe morbidity Mortality Survival (months) Arcidiacono [ 28 ] 2012, P Cryo-RFA Endoscopic, US 22 0% 0% mOS 6 D’Onofrio [ 16 ] 2017, P RFA Percutaneous, US 18 0% 0% mOS 6 Crino [ 27 ] 2018, P RFA Endoscopic, US 8 0% 0% NS Scopelliti [ 29 ] 2018, P RFA Endoscopic, US 17 0% 0% NS Carrafiello [ 17 ] 2013, R MWA Percutaneous/open (5/5), US and CT 10 20% 0% 1 yr = 80% Ierardi [ 18 ] 2018, R MWA Percutaneous, US and CT 5 0% 0% NS Vogl [ 19 ] 2018, R MWA Percutaneous, CT 22 0% 0% NS Niu [ 50 ] 2012, R Cryoablation Percutaneous, US and CT 11 0% …”
Section: Locoregional Ablation Brachytherapy Chemotherapy and Immunotherapymentioning
confidence: 99%
“…stages II, III, and IV) Liu [ 8 ] 2015, NS Brachytherapy ( 125 I seeds) ± TACE Percutaneous, CT 26 (incl. stages III and IV) NS NS mOS 17.6 (stage III) Yang [ 28 ] 2016, P Brachytherapy ( 125 I seeds) Percutaneous, CT 18 17% 0% mOS 7.3 Lv [ 29 ] 2017, R Brachytherapy ( 125 I seeds) Percutaneous, CT 32 Grade 2 +: 23% 1.3% NS Liu [ 9 ] 2012, R (syst rev) IAIC vs. Syst chemo Catheter, NS 298 (incl. stages III and IV) SAE NS 0% mOS: IAIC 5–21 Syst chemo 2.7–14 Liu [ 30 ] 2016, R IAIC Catheter, NS 235 NS NS mOS 7 (incl.…”
Section: Locoregional Ablation Brachytherapy Chemotherapy and Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…I n recent years, with the development of nuclear medicine and the treatment planning system (TPS) for iodine-125 ( 125 I), the advent of interstitial implant brachytherapy has been widely used in various malignant solid tumors, such as prostate cancer, pancreatic cancer, liver cancer, peripheral lung cancer, cancers of the head and neck, and other malignant tumors, and this has been proven to exhibit significant efficacy. [1][2][3][4][5][6][7][8][9] To date, the treatment of 125 I seed implantation has been mostly guided by computed tomography (CT). However, CT-guided percutaneous 125 I implantation remains limited for mediastinal lymph node metastasis and lung cancer due to the distance of the tumor from the skin, high risk of pneumothorax, and massive hemorrhage.…”
Section: Introductionmentioning
confidence: 99%